Influence of Work Discipline, Work Experience, and Compensation To Performance Employee d i Ministry of Industry, South Jakarta - Rizki Ahmad Fauzi; Ahmad Cik; Adam Nurkholik; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to analyze the effect of work discipline, work experience, and compensation on employee performance at the South Jakarta Ministry of Industry. The sample in this study was 80 respondents based on the Yamane formula. This study uses primary data with the method of collecting data through questionnaires distributed to 80 respondents. The data analysis technique used inferential analysis with multiple linear regression. The results obtained in this research are work discipline has a positive effect on employees performance, work experience has a positive effect on employee performance, and compensation has a positive effect on employee performance. Therefore, the Ministry of Industry should have a better impact so that Work Discipline, Work Experience, and Compensation can continue to be maintained stability.